An Efficient Cascade Synthesis of Ethyl 3-Amino-5-oxoisoxazolidine-4-carboxylate Derivatives - Li, Runrun; Wei, Qiang; Wang, Xin; Ge, Zemei; Li, Runtao (Synthesis, 2017)
An efficient cascade synthesis of ethyl 3-amino-5-oxoisoxazolidine-4-carboxylate derivatives from diethyl 2-(ethoxymethylene)malonate, different hydroxylamines and various amines is developed. This approach tolerates a wide range of amines affording highly functionalized isoxazolidine derivatives, which are expected to be important in organic synthesis and medicinal chemistry.
Keywords: isoxazolidines; cascade synthesis; mild conditions; amines; Michael addition